Peningkatan Hasil Belajar Pendidikan Kewarganegaraan Menggunakan E Modul - Usmiarti Usmiarti (INTECOMS: Journal of Information Technology and Computer Science, 2018)
This study aims to improve student learning outcomes in the subjects of Citizenship Education with the use of e-module in class X ADM SMEA Budi MuliaSolok. The type of research is classroom action research with the subject of the study of Class X X ADM SMEA Budi MuliaSolok in the even semester of the 2016/2017 Lesson Year with a total of 19 students. Techniques Data collection in this study is the test at the end of cycle I, cycle II and cycle III. Data were analyzed by using descriptive analysis technique and classical completeness. The result of the research showed that the result of the study of the students of Class X ADM SMEA Budi MuliaSolok after following the learning using e-module increased from cycle I to cycle II and to cycle III so that it can achieve classical mastery. So it can be concluded by using e-module student learning outcomes to be increased. Keywords: Learning Outcomes, E-Modules, Civic Education